CAUSAS DEL BAJO RENDIMIENTO ACADEMICO DE ESTUDIANTES DE LA CARRERA LICENCIATURA EN ADMINISTRACIÓN DE LA FACULTAD DE CIENCIAS ECONOMICAS Y ADMINISTRATIVAS DE LA UNIVERSIDAD NACIONAL DE ITAPUA, SEDE ENCARNACION (Journal on studies and research of academic knowledge, 2017)
This research is of exploratory transectional desing, focusing on the exploration of the causes of low academic performance of the students of the Bachelor of Administration in the Faculty of Economic and Administrative Sciences of the National University of Itapúa, headquarters Encarnación. The data collected from the surveys applied to students and teachers were analyzed quantitatively by descriptive and parametric statistics: test analysis t for independent samples and, subsequently, later contrasted with the qualitative data obtained by comparing the answers that the academic directors have given during the interviews. Finally, through a matrix of analysis, the consolidation of detected weaknesses and measures to be adopted was carried out. In the preliminary phase, documents, records and electronic files available at the institution were also reviewed. Among the main causes of students' low academic performance are: study strategies (academic factors), teaching and evaluation strategies (pedagogical factors), follow-up mechanisms for teaching management and the services offered by the career (institutional factors), age and the holding of children (demographic factors).
Keywords: Academic Performance; Factors; Educational Quality